2015
DOI: 10.1097/sla.0000000000000806
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticogastrostomy Is Superior to Pancreaticojejunostomy for Prevention of Pancreatic Fistula After Pancreaticoduodenectomy

Abstract: In PD, reconstruction by PG is associated with lower postoperative pancreatic and biliary fistula rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(77 citation statements)
references
References 28 publications
1
74
0
2
Order By: Relevance
“…It has been claimed that PG is a better pancreatic reconstruction method because it reduces the incidence and severity of POPF. Four recent meta-analyses based on eight randomized control trials have concluded that the POPF rate is significantly lower in PG than in PJ [28][29][30]. We recommended sutureless PG as an alternative to PJ because of the following advantages: (i) there is an absence of trans-pancreatic sutures because the trans-parenchymal sutures cause damage to the pancreatic tissues and leakage; (ii) PG is performed for a short time because of the proximity of the stomach to the pancreas; (iii) the stomach wall is well-vascularized and thick; (iv) there is early detection of intraluminal bleeding from the pancreatic remnant; (v) the pancreatic enzymes are inactive due to the high acidity in the stomach and a lack of enterokinase, which prevents a digestive damage to the PG; (vi) PG is isolated and is spaced apart from a. mesenterica superior, a. hepatica propria, v. portae and v. mesenterica superior; (vii) gastric decompression by a nasogastric tube eliminates gastric and pancreatic secretions, exerts less tension on PG, and can be used as a drainage if fistula occurs; and (viii) PG decreases the number of anastomoses in a single loop of jejunum, reducing the probability of loop kinking.…”
Section: Discussionmentioning
confidence: 99%
“…It has been claimed that PG is a better pancreatic reconstruction method because it reduces the incidence and severity of POPF. Four recent meta-analyses based on eight randomized control trials have concluded that the POPF rate is significantly lower in PG than in PJ [28][29][30]. We recommended sutureless PG as an alternative to PJ because of the following advantages: (i) there is an absence of trans-pancreatic sutures because the trans-parenchymal sutures cause damage to the pancreatic tissues and leakage; (ii) PG is performed for a short time because of the proximity of the stomach to the pancreas; (iii) the stomach wall is well-vascularized and thick; (iv) there is early detection of intraluminal bleeding from the pancreatic remnant; (v) the pancreatic enzymes are inactive due to the high acidity in the stomach and a lack of enterokinase, which prevents a digestive damage to the PG; (vi) PG is isolated and is spaced apart from a. mesenterica superior, a. hepatica propria, v. portae and v. mesenterica superior; (vii) gastric decompression by a nasogastric tube eliminates gastric and pancreatic secretions, exerts less tension on PG, and can be used as a drainage if fistula occurs; and (viii) PG decreases the number of anastomoses in a single loop of jejunum, reducing the probability of loop kinking.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding operative factors, the type of pancreatic anastomosis is chosen according to a surgeon's experience 3 . For reconstruction of the pancreas remnant after PD, two main methods of anastomosis have been described: pancreatogastrostomy and pancreatojejunostomy 22,29 . In a previous meta-analysis of seven randomized controlled trails, Liu et al 23 demonstrated that pancreatogastrostomy is more efficient than pancreatojejunostomy in reducing the incidence of clinically relevant pancreatic fistula.…”
Section: Figure 3 -Pancreatic Anastomosis and Protection (A-d)mentioning
confidence: 99%
“…Still, pancreatic surgery remains highly complex and is associated with significant morbidity and mortality rates (11)(12)(13). Therefore, when starting a robotic program for pancreatic surgery, it should be well prepared and several conditions must be met prior to performing the first procedures.…”
Section: Introductionmentioning
confidence: 99%